2020
DOI: 10.3390/w12020329
|View full text |Cite
|
Sign up to set email alerts
|

A Framework Proposal for Regional-Scale Flood-Risk Assessment of Cultural Heritage Sites and Application to the Castile and León Region (Central Spain)

Abstract: Floods, at present, may constitute the natural phenomenon with the greatest impact on the deterioration of cultural heritage, which is the reason why the study of flood risk becomes essential in any attempt to manage cultural heritage (archaeological sites, historic buildings, artworks, etc.) This management of cultural heritage is complicated when it is distributed over a wide territory. This is precisely the situation in the region of Castile and León (Spain), in which 2155 cultural heritage elements are reg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(18 citation statements)
references
References 35 publications
0
18
0
Order By: Relevance
“…The adopted methodology follows the common approach of combining hazard, vulnerability, exposure, and capacity to assess risk, but with a quantification of resilience, indirect impacts and an original declination of the concepts of exposure and vulnerability. With respect to existing works that examined flood risk to CH by combining hazard maps and heritage typologies as main parameter for a qualitative vulnerability classification at national or regional scale (Figueiredo et al, 2019; Garrote & Escudero, 2020), this work focuses on the intermediate scale of site where numerous CH is present, that is, an art city. The resilience model here introduced allows to quantify the system dynamics which is crucial to evaluate the time needed to recover after an event, this aspect has been rarely investigated for CH.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The adopted methodology follows the common approach of combining hazard, vulnerability, exposure, and capacity to assess risk, but with a quantification of resilience, indirect impacts and an original declination of the concepts of exposure and vulnerability. With respect to existing works that examined flood risk to CH by combining hazard maps and heritage typologies as main parameter for a qualitative vulnerability classification at national or regional scale (Figueiredo et al, 2019; Garrote & Escudero, 2020), this work focuses on the intermediate scale of site where numerous CH is present, that is, an art city. The resilience model here introduced allows to quantify the system dynamics which is crucial to evaluate the time needed to recover after an event, this aspect has been rarely investigated for CH.…”
Section: Discussionmentioning
confidence: 99%
“…The assessment of disaster losses on cultural heritage has not received enough attention so far and is considered quite challenging due to the multidimensionality of the problem (Romão et al, 2020;UNDP, 2013). Romão and Paupério (2021) As a consequence of the difficulties in quantifying exposure and vulnerability, flood risk assessment to cultural heritage has been mostly addressed in a qualitative way by categorizing and ranking assets in terms of vulnerability and performing exposure analysis at national or site scale Figueiredo et al, 2019;Garrote & Escudero, 2020;Miranda & Ferreira, 2019;Vojinovic et al, 2016;Wang, 2015). Flood vulnerability models for CH, that is, stage-damage functions are rarely found in literature (Figueiredo et al, 2021), since only recently the Sendai Framework has identified the promotion of resilient CH under the broad priority action areas.…”
Section: Introductionmentioning
confidence: 99%
“…Vulnerability curves and indicator‐based methodologies are the two main methods for assessing physical vulnerability (Papathoma‐Köhle, 2016). Vulnerability matrices are another method applied for landslides, debris flows, or floods (e.g., Garrote, Díez‐Herrero, Escudero, & García, 2020; Hu, Cui, & Zhang, 2012; Leone, Asté, & Leroi, 1996; Rojas, Mardones, Rojas, Martínez, & Flores, 2017), although impaired by high subjectivity involved (Papathoma‐Köhle et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Flood risk of cultural heritage has been recently analyzed at regional scale in Spain and at national scale in Portugal with a semi-quantitative approach based on hazard maps and vulnerability classification of heritage typology (Figueiredo et al, 2019;Garrote et al, 2020). At site scale, a flood risk framework has been applied to the historical city of Alzira (Spain) with a detailed catalog of morphological and constructive characteristics of monuments (Trizio et al, 2021).…”
Section: Introductionmentioning
confidence: 99%